Quercetin Protects against Obesity-Induced Skeletal Muscle Inflammation and Atrophy. (28th December 2014) - Le, Ngoc Hoan; Kim, Chu-Sook; Park, Taesun; Park, Jung Han Yoon; Sung, Mi-Kyung; Lee, Dong Gun; Hong, Sun-Myung; Choe, Suck-Young; Goto, Tsuyoshi; Kawada, Teruo; Yu, Rina
Abstract : Skeletal muscle inflammation and atrophy are closely associated with metabolic impairment such as insulin resistance. Quercetin, a natural polyphenol flavonoid, is known to elicit anti-inflammatory and antioxidant activities. In this study, we investigated its effect on obesity-induced skeletal muscle inflammation and atrophy in mice. Male C57BL/6 mice were fed a regular diet, a high-fat diet (HFD), and an HFD supplemented with quercetin for nine weeks. Quercetin reduced levels of inflammatory cytokines and macrophage accumulation in the skeletal muscle of the HFD-fed obese mice. It also reduced transcript and protein levels of the specific atrophic factors, Atrogin-1 and MuRF1, in the skeletal muscle of the HFD-fed obese mice, and protected against the reduction of muscle mass and muscle fiber size. In vitro, quercetin markedly diminished transcript levels of inflammatory receptors and activation of their signaling molecules (ERK, p38 MAPK, and NF-κ B) in cocultured myotubes/macrophages, and this was accompanied by reduced expression of the atrophic factors. Together, these findings suggest that quercetin reduces obesity-induced skeletal muscle atrophy by inhibiting inflammatory receptors and their signaling pathway. Quercetin may be useful for preventing obesity-induced muscle inflammation and sarcopenia.